The Orizing Online Game Applications With Islamic Content To Foster Youth’s Willingness To Learn Islam - Haira Rizka (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
Online gaming becomes popular among youth with the fast emergence of internet use. Various types of games are available and free to download on gadgets. Millennial game developers also utilize this condition to build online application games with Islamic content. This paper aims to investigate sorts of online game applications with Islamic contents and analyze Muslim youth's perspectives on the phenomenon. This research employs the religion and virtual reality theory of Bainbridge (2014). This descriptive qualitative research collected the data through textual study and interviews. The collected data were analyzed by employing textual analysis and ethnography methods. The research reveals two primary results. First, there are three most popular religious game applications; they are Cerdas Cermat Islami (rated 4.7 with 100,000 active users), Kuis Pengetahuan Islam (4.7 with 10,000 active users), and Muslim Millionaire (4.6 with 100,000 active users). The three applications provide challenging puzzles, activities, and challenges with Islamic content. In other words, while entertaining themselves, gamers learn Islamic knowledge. Second, the gamers' comments indicate that they are satisfied with the games and the contents. Furthermore, they get more benefits by learning more knowledge about Islam in more amusing media. Game is probably a more effective media to foster youth learn Islam.